Galectins in channel catfish, Ictalurus punctatus: Characterization and expression profiling in mucosal tissues. (February 2016) - Zhou, Shun; Zhao, Honggang; Thongda, Wilawan; Zhang, Dongdong; Su, Baofeng; Yu, Dan; Peatman, Eric; Li, Chao
Abstract: Galectins, a family of β-galactoside-binding lectins with conserved CRDs, which can recognize the glycans on the surface of viruses, bacteria and protozoan parasites, are emerging as key players in many important pathological processes, including acute and chronic inflammatory diseases, autoimmunity and apoptosis. Although galectins have attracted great interest in mammals, they are still poorly-characterized in teleost. Previously, several studies have reported their high expression levels in mucosal tissues before and post infection. Given the important roles for galectins in mucosal immunity, therefore, we characterized the galectin gene family and profiled family member expression after challenge with two different Gram-negative bacterial pathogens. Here, twelve galectins genes were captured in channel catfish ( Ictalurus punctatus ), and phylogenetic analysis showed the strongest relationship to zebrafish and salmon, which is consistent with their phylogenetic relationships. Furthermore, the galectin genes were widely expressed in catfish tissues, while most of the galectin genes were strongly expressed in mucosal tissues (skin, gill and intestine). In addition, the expression profiles of galectins after bacterial infection varied depending on both pathogen and tissue type, suggesting that galectins may exert disparate functions or exhibit distinct tissue-selective roles in the host immune response to bacterial pathogens. Further studies are needed, however, to expand functional characterization and examine whether galectins may also play additional physiological roles in catfish immunity. Highlights: Twelve galectin genes were identified in channel catfish. Galectin genes were ubiquitously expressed in catfish tissues. Galectin genes were significantly induced after bacterial challenge.